Zielgerichtete Therapie des Mammakarzinoms - Seiffert, Katharina; Schmalfeldt, Barbara; Müller, Volkmar (DMW - Deutsche Medizinische Wochenschrift, 2017)
Within the last years, significant improvements have been achieved in breast cancer treatment, particularly with the development of targeted therapies. Major progress has been made in identifying the drivers malignant growth in oestrogen-receptor-positive breast cancer and the mechanisms of resistance to endocrine therapy. This progress has translated into several targeted therapies that enhance the efficacy of endocrine therapy; inhibitors of the cyclin-dependent kinases CDK4 and CDK6 like palbociclib and inhibitors of mTOR substantially improve progression-free survival. For patients with HER2-positive disease the addition of Pertuzumab to Trastuzumab in combination with chemotherapy has been a significant improvement in anti-HER2 therapy in early as well as metastatic breast cancer. Evidence-based further line therapy options in the metastatic setting include T-DM1 and in later lines Lapatinib. For triple negative disease the angiogenesis inhibitor Bevacizumab is approved, which increases progression free survival. Immune checkpoint inhibitors, PARP-inhibitors or anti-androgens represent promising strategies, all of which are currently being evaluated in clinical trials. The development of predictive biomarkers to guide targeted therapies is still the subject of research.
Keywords: Brustkrebs; zielgerichtete Therapie; HER2; Hormonrezeptor; triple-negativ